DEVELOPMENT OF DIGITAL STUDENT ACTIVITY SHEETS AS LEARNING MEDIA IN HYBRID LEARNING - Fitri Aldresti; Erviyenni Erviyenni; Betty Holiwarni; Sri Haryati; Yanni Irma Waty Simanjuntak (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This Research aims to develop a digital student worksheet for hybrid learning that is valid and practically reviewed based on student responses as users. Digital student worksheet can be used as teaching materials that help students in hybrid learning. This research and development consist of three stages, namely define, design, and develop. The research data was obtained through a validation sheet by two expert validators based on aspects of content feasibility, aspects of didactic feasibility, aspects of language feasibility, aspects of presentation feasibility and aspects of graphic feasibility with response questionnaire for digital worksheet users. Based on the results of expert validation, the percentage are 93.75% on content feasibility; 83.33 % on didactic feasibility; 89.58% on language feasibility; 83.33% on presentation feasibility; and 83.33% on graphic feasibility. The percentage as result of questionnaire for digital worksheet users is 89.47%. Students’ responses as users show that digital worksheet is practical, easy to access, and can increase interest in learning. So, the average of digital worksheet validity percentage is 86.66% and it can be concluded that the digital student worksheet for hybrid learning which is developed using the Microsoft Sway application is categorized as very valid and can be used as a learning media.